Pengaruh Program Magang Dan Studi Independen Bersertifikat (MSIB) Terhadap Peningkatan Self-Confidence Dan G Kerja Mahasiswa Universitas Hamzanwadi - Ramdani, Dheta Alvina; Majdi, Muhammad Zainul (Alpatih Harapan Semesta, 2024)
This study aims to identify the impact of the internship program and certified independent study (MSIB) on Self-confidence and job opportunities of Hamzanwadi University students. The design in this study is a descriptive quantitative type of primary and secondary data used were collected through the distribution of survey questionnaires and data from the Coordinator of the MSIB Program of Hamzanwadi University. This population is students who take part in the MSIB program at Hamzanwadi University as many as 61 samples. To collect samples, total sampling techniques or census sampling were used. The data were processed using SPSS statistics ver. 22 with several tests, namely hypothesis analysis, classical assumption tests, and multiple linear regression. Based on the data processing process, between the internship variable and student self-confidence with a t table value smaller than the calculated t (2.002 < 2.705) there is a positive influence, without any significant impact between the internship variable and student job prospects with a t table value > calculated t (2.002 > -0.586), the independent study variable on self-confidence with a lower calculated t value than the t table (1.784 < 2.002), the independent study variable on job opportunities with a higher t table value than the calculated t (2.002 > 0.863), simultaneously there is a large effect between the internship variable, certified independent study (MSIB) on self-confidence with a table F value greater than the calculated F value (11.631 > 3.16) and significantly affects the internship variable, certified independent study (MSIB) on job opportunities with a calculated F value < F table (1.210 < 3.16). In R square (R2) on variable Y1, the result is 26.2% and Y2 is 0.7%, meaning that self-confidence and job opportunities for students can be explained by internship variables and certified independent studies and the remaining 73.8% and 99.3% can be known from the influence of variables outside this study.